B-type natriuretic peptide secretion following scuba diving. (April 2011) - Passino, Claudio; Franzino, Enrico; Giannoni, Alberto; Prontera, Concetta; Goetze, Jens Peter; Emdin, Michele; Clerico, Aldo
Aim: To examine the neurohormonal effects of a scuba dive, focusing on the acute changes in the plasma concentrations of the different peptide fragments from the B-type natriuretic peptide (BNP) precursor.Materials & methods: We studied 12 healthy scuba divers (mean age ±± standard deviation: 44 ±± 7 years; range: 34––55 years; BMI: 24.8 ±± 2.8 kg/m 2 ), who performed a 15-m depth dive in salt water, with a bottom time of 30 min. Blood samples for BNPs (pro-B-type natriuretic peptide [pro-BNP], BNP and aminoterminal pro-BNP) and catecholamines were measured in plasma before immersion, and after the dive. A continuous electrocardiographic recording was obtained during the entire protocol.Results: BNP, aminoterminal pro-BNP and pro-BNP plasma concentrations slightly, but significantly, increased after the scuba dive (18 ±± 15 to 21 ±± 11 ng/l, p = 0.020; 32 ±± 19 to 38 ±± 21 ng/l, p = 0.008; and 7.8 ±± 1.6 to 10.3 ±± 3.6 ng/l, p = 0.028, respectively) in parallel with norepinephrine concentration (743 ±± 323 to 1163 ±± 656 ng/l, p = 0.014), with no variations in total plasma proteins, hematocrit or osmolality. A persistent sinus tachycardia was observed during all phases of the dive.Conclusions: A 15-m depth scuba dive induces an acute slight release of the different peptide fragments from the BNP precursor, likely through the stimulation of a constitutive secretory pathway promoted by adrenergic activation and cardiac chamber dilation.